Household labor supply and home services in a general-equilibrium model with heterogeneous agents - Christian Bredemeier; Falko Jüßen (Institute for the Study of Labor (IZA), 2009)
We propose a new explanation for differences and changes in labor supply by gender and marital status, and in particular for the increase in married women's labor supply over time. We argue that this increase as well as the relative constancy of other groups' hours are optimal reactions to outsourcing labor in home production becoming more attractive to households over time. To investigate this hypothesis, we incorporate heterogeneous agents into a household model of labor supply and allow agents to trade home labor. This model can generate the observed patterns in US labor supply by gender and marital status as a reaction to declining frictions on the market for home services. We provide an accounting exercise to highlight the role of alternative explanations for the rise in hours in a model where home labor is tradable.
urn:nbn:de:101:1-20090209140
Keywords: J22; J16; E13; D13; 330; Labor supply; gender; home production; heterogeneity; Arbeitsangebot; Haushaltsökonomik; Frauenerwerbstätigkeit; Ehe; Hausarbeit; Outsourcing; Theorie; USA